Serena the salsa fairy - Meadows, Daisy (New York : Scholastic, 2009)
All of the fun at the fiesta in Wetherbury will be ruined if the magic ribbons can't be found.
RL2.
006-009.
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Fiction; Tate, Kirsty (Fictitious character) -- Fiction; Fairies -- Fiction; Fantasy fiction